Climate Change Denial Books and Conservative Think Tanks: Exploring the Connection. (June 2013) - Dunlap, Riley E.; Jacques, Peter J.
The conservative movement and especially its think tanks play a critical role in denying the reality and significance of anthropogenic global warming (AGW), especially by manufacturing uncertainty over climate science. Books denying AGW are a crucial means of attacking climate science and scientists, and we examine the links between conservative think tanks (CTTs) and 108 climate change denial books published through 2010. We find a strong link, albeit noticeably weaker for the growing number of self-published denial books. We also examine the national origins of the books and the academic backgrounds of their authors or editors, finding that with the help of American CTTs climate change denial has spread to several other nations and that an increasing portion of denial books are produced by individuals with no scientific training. It appears that at least 90% of denial books do not undergo peer review, allowing authors or editors to recycle scientifically unfounded claims that are then amplified by the conservative movement, media, and political elites.